Hubungan Pemberian Asi Eksklusif Dengan Kejadian Common Cold Pada Bayi 6-12 Bulan Di Wilayah Puskesmas Kartasura - Sari, Yulita Purnama, Dr. Arne Laksmiasanti, Sp.THT-KL., M.Kes (2017)
Background : One infectious disease incidence rates quite often both globally and in Indonesia is the common cold. Common cold is also called the Upper Respiratory Tract Infection (ARI) is a primary infection in the nasopharynx and nasal discharge that often, the disease is often found in infants and children. World Health Organiation (WHO) said that ISPA can be prevented with exclusive breastfeeding. Purpose : Purpose of the research is to know relationship between exclusive breastfeeding and common cold incidents among 6-12 months old babies. Method : The research used descriptive-analytical design with cross-sectional approach. Sample of the research was 61 respondents taken by using purposive sampling technique and data was collected by using questionnaire and interview. Sample of the research was 6-12 months old babies in working region of Puskesmas Kartasura on November 2016. Results : The research found that frequency of common cold was lesser in group of exclusive breastfeeding than in non-exclusive breastfeeding group. Results of hypothetic test with Kolmogorov-Smirnov obtained p-value < 0.001. Conclusion: The research found a significant correlation between exclusive breastfeeding and common cold incident among 6-12 months old babies in working region of Puskesmas Kartasura.